Revitalisation of the agua de mina waste dam for aquaculture, livestock raising and wildlife habitat - Adams, R. H.; Guzmán-Osorio, F. J.; Domínguez-Rodríguez, V. I. (The Institution of Engineers, Malaysia (IEM), 2012)
Link to publisher’s homepage at http://www.myiem.org.my/